Empatia, etica e trattamento psicoanalitico - Rotella, Ivan (Bollettino Filosofico, 2022)
The contribution aims to investigate the role of empathy into psychoanalysis and, consequently, if and how Freudian psychoanalysis can offer a theoretical model for interpreting the role that empathy plays within ethical reflection. For this reason, it will be necessary, at first, to investigate if it is really possible to talk about empathy within the psychoanalytic technique and, than, to investigate how Freudian technique uses empathy. Finally, by relating the two essays Recommendations to physicians practising psycho-analysis (1912) and On Beginning the Treatment (1913), empathy appears like a paradoxical node in Freudian reflection: on the one hand, a necessary tool for starting the analytic relationship, but, at the same time, on the other hand, an object necessarily excluded from the technique for ending the analytic relationship. Keywords: Empathy, Ethics, Freud, Lipps, Psychoanalysis